3D hydrogen-like screening effect on excitons in hBN-encapsulated monolayer transition metal dichalcogenides - S. Takahashi; S. Kusaba; K. Watanabe; T. Taniguchi; K. Yanagi; K. Tanaka (Scientific Reports)
Abstract We observe both s-series and p-series excitons by using sum frequency generation spectroscopy on monolayer (1L-)MX2 (M = Mo, W, X = S, Se) encapsulated by hexagonal boron nitride (hBN). Moreover, we perform numerical calculations with the Rytova-Keldysh potential and obtain the relative dielectric constant of hBN among other parameters. The obtained relative dielectric constant can be approximated by the high-frequency limit of the infrared dispersion even though the exciton binding energies are almost on the phonon resonances in hBN. This suggests that the theoretically indicated modification of the exciton level structure due to the phonon resonances is negligible. The power-law scaling of exciton binding energies indicates that dielectric screening of 1L-MX2 exciton levels other than 1s can be approximated by that of a 3D hydrogen model with the dielectric constant of hBN.